ANALISIS ALIRAN DARAH DALAM PEMBULUH ARTERI MENGGUNAKAN PERSAMAAN NAVIER-STOKES DAN METODE LATTICE-BOLTZMANN - HUDOARMA, FATHURAHMAN MA’RUF; GUNAWAN, P. H.; ROHMAWATI, ANIQ A. (E-Jurnal Matematika; Vol 7 No 2 (2018), 2018)
This simulation was performed to analyze arterial blood flow using Navier-Stokes equations and LatticeBoltzmann method with Bhatnagar-Gross-Krook approach to obtain an explicit form of the LatticeBoltzmann Bhatnagar-Gross-Krook equations. Then by adding some cases of plaque on simulation domain, changes in arterial blood flow pressure can be analyzed. The area and shape of the plaque cause narrowing the artery vessels that affect the pressure and rate of blood flow dynamically. The pressure of blood flow without plaque is stable ranged from 17 to 19 Pa. While in the vessels with plaque, blood flow pressure increased significantly up to 35.145 Pa.